The Effect of Social Entrepreneurship, Government Support on Local Economic Performance in Indonesia, and the Impact of Local Initiatives Mediated by Intellectual Capital - Rahmaddian Rahmaddian (Westscience Press, 2024)
This study explores the relationship between intellectual capital, government support, social entrepreneurship, and local economic success in Indonesia. Data were gathered from a broad sample of respondents who represented local businesses, government authorities, and social entrepreneurs using a quantitative research approach. The study utilized structural equation modeling (SEM) in conjunction with partial least squares (PLS) analysis to investigate the correlations between the variables. The results show that social entrepreneurship and government assistance have a major positive impact on local economic performance. It was also shown that intellectual capital acted as a mediator in these partnerships, underscoring its critical function in converting government assistance and social entrepreneurship into concrete economic results. The study highlights the significance of creating an environment that is supportive of entrepreneurship and innovation and advances our knowledge of the mechanisms driving economic progress in Indonesia. The knowledge gained from this study has important ramifications for stakeholders, practitioners, and policymakers who want to encourage local sustainable economic growth.